The Digital Governance Gap in Southeast Asia: A Comparative Study of Indonesia, India, and the Philippines - Junaedi Rahmansya; Arjun Mehta; Mark Joseph Bautista (Asian Digital Governance Problems, 2025)
Purpose: This study examines digital governance disparities in Indonesia, India, and the Philippines by analyzing how institutional coordination, administrative capacity, and governance structures influence digital transformation outcomes in developing democracies. Subjects and Methods: The research employed a qualitative comparative design using semi-structured interviews, policy documents, and institutional reports collected between 2023 and 2024. Data were analyzed through thematic content analysis supported by institutional capacity theory and digital governance maturity frameworks. Results: The findings reveal that India demonstrates stronger policy coherence and institutional integration through centralized coordination under the Digital India initiative, while Indonesia experiences fragmented implementation caused by decentralized governance and uneven regional administrative capacity. The Philippines exhibits relatively strong local innovation and participatory governance practices, although implementation continuity remains vulnerable to political transitions. Digital governance effectiveness across the three countries is strongly influenced by bureaucratic adaptability, institutional continuity, inter-agency coordination, and digital inclusivity rather than technological infrastructure alone. Conclusions: Sustainable digital transformation requires adaptive institutions, coherent governance systems, inclusive participation mechanisms, and long-term administrative coordination to achieve equitable and effective digital governance.